AMALAN PENDIDIKAN KANAK-KANAK DALAM ISLAM: PRACTICE OF CHILD EDUCATION IN ISLAM - Almuddin, Mohd Hasem; Jamil, Asyraf Isyraqi; Sa’ari, Che Zarrina (Journal of Islamic Educational Research, 2016)
Child education is a subject which has been debated and focused in the world of Islamic education. This can be seen in the Muslim intellectual tradition. This article collects and analyzes the views of past and contemporary Islamic scholars through their writings which are related to the child education. Documentation method is used in the data collection. Moreover, content analysis method is used in the data analysis which includes inductive, deductive and comparative methods. Few aspects have been mainly emphasized by the Islamic scholars in the practice of child education in Islam. These involve the importance and history of child education as well as the concept, principle and phases of child education in Islam.